Elastic and radiation shielding properties of zinc borotellurite glass systems: The impact of gadolinium oxide - Mohd Haniff bin Mohd Tahir (Tanjung Malim, 2024)
Elastic and radiation shielding properties of zinc borotellurite glass systems: The impact of gadolinium oxide by Mohd Haniff bin Mohd Tahir